(untitled) (Urdimento: Revista de Estudos em Artes Cênicas, 2022)
This article analyzes two productions by Cia Livre, presented in 2019, based on the learning play The Horatians and the Curiatians (1933), by Brecht, and which thematize the struggle for land in Brazil today. This confrontation was synthesized, in Death and Dependence in the Land of Pau-Brasil and The One and the Others, as a dispute between the people of the One (people who consider themselves universal) and the people of the Others (all other peoples, with their human, extra-human, animal, plant and mineral cultures.) The critique of the aesthetic-philosophical model of Euro-Western theater carried out here observes the contradictions created by the presence of indigenous and non-indigenous interpreters, which mirror the dissensions and coalitions between different perspectives of emancipatory struggles. How were their experiences translated into the scene? What kind of sociability was projected there? What theatrical form can emerge from the experience of decentralization of the western subject that the group indicates in these works?